AMERICAN DREAM IN JOHN STEINBECK’S THE GRAPES OF WRATH AND JEFFREY ARCHER’S KANE AND ABEL (Universitas Islam Negeri Sunan Ampel Surabaya, 2014)
This article attempts to analyze the American Dream in John Steinbeck’s The Grapes of Wrath and Jeffry Archer’s Kane and Abel. The article uses American Dream Concepts and Historical background to analyze the characters. The study aims at comparing two different literary works coming from two different cultures, nationalities, and historical background. The articlestudies the concepts of the American Dream which holds three key points, better, richer, and fuller life with opportunity according to ability or achievement.The results of this article can be formulated as follows: 1) Both have the American Dream and different achievements and effort to gain the American Dream through the representation of the characters of Ma Joad in The Grapes of Wrath whose American Dream is unattainable and Abel in the Kane and Abel whose American Dream is attainable. (2) Both Ma Joad and Abel struggle to concretize the American Dream while Ma Joad cannot achieve the American Dream through her hard effort. Abel achieves the American Dream. Therefore, Ma Joad’s mobility is downward, while Abel’s is upward. (3) The similarities of the two novels are the descriptions of the main characters that are poor people to achieve and struggle for the American Dream.